2020
DOI: 10.3390/cells9010152
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Melatonin and Dopamine D3 Receptor Heteromers in Eye Ciliary Body Epithelial Cells and Negative Correlation with Ocular Hypertension

Abstract: Background: Experiments in the late nineties showed an inverse relationship in the eye levels of melatonin and dopamine, thereby constituting an example of eye parameters that are prone to circadian variations. The underlying mechanisms are not known but these relevant molecules act via specific cell surface dopamine and melatonin receptors. This study investigated whether these receptors formed heteromers whose function impact on eye physiology. We performed biophysical assays to identify interactions in hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…D3Rs were demonstrated in peripheral organs such as the kidney [ 53 ] and by PET in the human retina [ 54 ]. In the human eye D3Rs were identified in the ciliary body epithelial cells where they heteromerized with melatonin-1 and melatonin-2 receptors [ 55 ]. D3Rs were found in the pancreas [ 56 ] and are thought to be involved in insulin secretion.…”
Section: D3rs In the Brain And Peripherymentioning
confidence: 99%
“…D3Rs were demonstrated in peripheral organs such as the kidney [ 53 ] and by PET in the human retina [ 54 ]. In the human eye D3Rs were identified in the ciliary body epithelial cells where they heteromerized with melatonin-1 and melatonin-2 receptors [ 55 ]. D3Rs were found in the pancreas [ 56 ] and are thought to be involved in insulin secretion.…”
Section: D3rs In the Brain And Peripherymentioning
confidence: 99%
“…It has been reported that D3R plays an important role in neurogenesis and neuropsychiatric disorders mainly through MAPK, AKt and CREB signaling pathways [21,[32][33][34]. Thus we next screen a series of related signaling pathways that may participate in D3R inhibition-induced microglia activation in cultured BV-2 cell line.…”
Section: Effects Of Akt Signaling Pathway On Microglia Activation Induced By D3r Inhibitionmentioning
confidence: 99%
“…More recently, heterodimers containing the D3R and either the MT1 or MT2 melatonin receptors have been detected in both transfected cells and in human eye postmortem tissues, where they are thought to regulate intraocular pressure. This heterodimerization abolishes D3R-Gi coupling and signaling to the Erk1/2 pathway [ 67 ]. Beside GPCRs, other structurally and functionally different classes of receptors, as ion channel receptors, may interact with D3R [ 68 ] ( Table 1 ).…”
Section: D3 Receptor Heteromerizationmentioning
confidence: 99%
“…In particular, we recently reported a direct interaction of D3R with the nicotinic acetylcholine receptor (nAChR) [20]. FRET and BRET in transfected cell lines [14,54] Parkinson's disease [14,54,62] CO-IP in transfected cell lines and rat striatum [54] Addiction [56,62] PLA in rat and monkey striatum [69] LID [54,56,62,69] D2R-D3R CO-IP in transfected cell lines [50] Parkinson's disease [51,63] Schizophrenia [51] Other GPCRs D3R-A2AR FRET in transfected cell lines [64] Parkinson's disease [64] Schizophrenia [64] D3R-MT1R/MT2R BRET in transfected cell lines [67] Intraocular pressure [67] PLA in human non-pigmented ciliary body epithelial cells [67] Ion Channels D3R-nAChR BRET in transfected cell lines [20] Parkinson's disease [19,20] PLA in mouse primary mesencephalic DA neurons and midbrain sections [20], and in hiPSC-derived DA neurons [19] Addiction [20] Abbreviations: A2AR, adenosine A2A receptor; BRET, bioluminescence resonance energy transfer; CO-IP, co-immunoprecipitation; DA, dopamine; D1R, dopamine D1 receptor; D2R, dopamine D2 receptor; D3R, dopamine D3 receptor; FRET, fluorescence resonance energy transfer; GPCRs, G-protein coupled receptors; LID, L-DOPA-induced dyskinesia; MT1R/MT2R, melatonin receptor 1 and 2; nAChR, nicotinic acetylcholine receptor; PLA, proximity ligation assay.…”
Section: D3 Receptor Heteromerizationmentioning
confidence: 99%